2008
DOI: 10.1152/ajprenal.00419.2007
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ-induced RhoA activation and fibronectin production in mesangial cells require caveolae

Abstract: Glomerular sclerosis of diverse etiologies is characterized by mesangial matrix accumulation, with transforming growth factor-beta (TGFbeta) an important pathogenic factor. The GTPase RhoA mediates TGFbeta-induced matrix accumulation in some settings. Here we study the role of the membrane microdomain caveolae in TGFbeta-induced RhoA activation and fibronectin upregulation in mesangial cells (MC). In primary rat MC, TGFbeta1 time dependently increased RhoA and downstream Rho kinase activation. Rho pathway inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 65 publications
6
61
1
Order By: Relevance
“…Along with cancer metastasis studies, the current study suggested that RhoA-inducing TAK1 was a modulator of epithelial motility and contributes to normal tissue integrity by promoting cell migration and restitution of the injured tissues. In terms of mechanism, the current study addressed the effects of NAG-1-linked TAK1 on the induction of RhoA expression, supporting some connections between the TGF-b superfamily and RhoA signaling activation have been reported (24,28). In these previous studies, RhoA expression was not altered, but only RhoA activity was enhanced.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Along with cancer metastasis studies, the current study suggested that RhoA-inducing TAK1 was a modulator of epithelial motility and contributes to normal tissue integrity by promoting cell migration and restitution of the injured tissues. In terms of mechanism, the current study addressed the effects of NAG-1-linked TAK1 on the induction of RhoA expression, supporting some connections between the TGF-b superfamily and RhoA signaling activation have been reported (24,28). In these previous studies, RhoA expression was not altered, but only RhoA activity was enhanced.…”
Section: Discussionsupporting
confidence: 74%
“…As the central downstream mediators of signaling pathway of TGF-b superfamily NAG-1, smads at convergent points of TGF-b receptor-linked pathway can be activated to RhoA GTPase. However, it has been well documented that RhoA activation is independent of smad-linked signaling pathways (23,24). Therefore, we focused on another target of TGF-b receptor-linked pathway, TAK1, as a mediator of NAG-1-induced RhoA activity.…”
Section: Discussionmentioning
confidence: 99%
“…This regulation is known to act most commonly in an inhibitory fashion, with release from caveolin-1 enabling activation (Razani et al, 2002). However, positive regulatory functions have also been demonstrated, as are seen in insulin receptor signaling and transforming growth factor-beta (TGFβ)-induced Rho A activation processes (Yamamoto et al, 1998;Peng et al, 2008). In our studies, H 2 O 2 -mediated SHP-2/ERK phosphorylation was reduced in astrocytes by caveolin-1 siRNA, suggesting that caveolin-1 may function as a positive regulator in SHP-2/ERK signaling pathways in response to H 2 O 2 in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of fasudil on the phosphorylation of Src and caveolin-1 in diabetic glomeruli Src-family kinases are the only known caveolin-1 Y14 kinases [24,25] , and our previous studies demonstrated that TGF-β-and VEGF-induced Src activation mediated caveolin-1 phosphorylation at Y14 followed by fibronectin synthesis in mesangial cells [23,26] . Because fasudil prevented VEGF upregulation in diabetic kidneys, we investigated the effect of fasudil on Src and caveolin-1 phosphorylation levels.…”
Section: Wwwchinapharcom Jin J Et Almentioning
confidence: 98%